Importance of Sequence and Timing in Parasite Coinfections. Issue 2 (February 2019) - Karvonen, Anssi; Jokela, Jukka; Laine, Anna-Liisa
Abstract : Coinfections by multiple parasites predominate in the wild. Interactions between parasites can be antagonistic, neutral, or facilitative, and they can have significant implications for epidemiology, disease dynamics, and evolution of virulence. Coinfections commonly result from sequential exposure of hosts to different parasites. We argue that the sequential nature of coinfections is important for the consequences of infection in both natural and man-made environments. Coinfections accumulate during host lifespan, determining the structure of the parasite infracommunity. Interactions within the parasite community and their joint effect on the host individual potentially shape evolution of parasite life‐history traits and transmission biology. Overall, sequential coinfections have the potential to change evolutionary and epidemiological outcomes of host–parasite interactions widely across plant and animal systems. Highlights: Parasite coinfections are common throughout plant and animal kingdoms. The resulting parasite–parasite interactions can potentially influence parasite traits such as infection success and virulence. Coinfections of multiple parasites can occur simultaneously, but more often sequentially, with a gap of time between the infections. This can dramatically change the outcome of coinfection. Sequential and repeated infection events are very common in nature. Regardless, research on coinfections has largely focused on simultaneous attack by multiple parasites. Sequential coinfections have also implications for parasite epidemiology and prevention. Designing disease-prevention strategies that account for coinfections and their timing could significantly improve success of intervention efforts.